2018
DOI: 10.5194/amt-11-6525-2018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a warehouse fire smoke plume over Paris with an N<sub>2</sub> Raman lidar and an optical thickness matching algorithm

Abstract: Abstract. A smoke plume, coming from an accidental fire in a textile warehouse in the north of Paris, covered a significant part of the Paris area on 17 April 2015 and seriously impacted the visibility over the megalopolis. This exceptional event was sampled with an automatic N2 Raman lidar, which operated 15 km south of Paris. The industrial pollution episode was concomitant with the long-range transport of dust aerosols originated from the Sahara, and with the presence of an extended stratus cloud cover. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…An increasing interest in pollen has arisen in the aerosol lidar community (Noh et al, 2013;Sicard et al, 2016). In our previous study (Bohlmann et al, 2019) we showed on the basis of an 11 d birch pollination period that lidar measurements can detect the presence of pollen grains in the atmosphere and that non-spherical pollen grains can generate strong depolarization (we found a mean depolarization ratio of 0.26 for the birch-spruce pollen mixture).…”
Section: Introductionmentioning
confidence: 50%
“…An increasing interest in pollen has arisen in the aerosol lidar community (Noh et al, 2013;Sicard et al, 2016). In our previous study (Bohlmann et al, 2019) we showed on the basis of an 11 d birch pollination period that lidar measurements can detect the presence of pollen grains in the atmosphere and that non-spherical pollen grains can generate strong depolarization (we found a mean depolarization ratio of 0.26 for the birch-spruce pollen mixture).…”
Section: Introductionmentioning
confidence: 50%
“…The simulator includes a direct model and an inverse model modules (the block diagram is shown in Fig. S1 in the supplement); Similar ones have already been used for forest and aerosol studies (Shang et al, 2018;Shang and Chazette, 2015).…”
Section: Simulatormentioning
confidence: 99%
“…To evaluate the MAPIR profiles in Sect. 5.3.2, the Klett inversion method (Klett, 1981) is applied to retrieve the aerosol backscatter coefficients and aerosol extinction coefficients at 355 and 532 nm, using lidar ratios of ∼ 45 and ∼ 35 sr, which are derived using Raman inversion for nighttime lidar measurements (method description in Ansmann et al, 1990;Shang et al, 2018). The volumetric depolarization ratio (VDR) and linear particle depolarization ratio (PDR) at 355 and 532 nm are also derived following the procedure described in Chazette et al (2012).…”
Section: Al Dhaid Lidarmentioning
confidence: 99%
“…In addition, the radiative transfer model requires some microphysical properties of the aerosols. We have chosen to maintain the parameters used in previous versions of MAPIR (Vandenbussche et al, 2013): a lognormal particle size distribution (PSD) with a median radius of 0.6 µm and a geometric standard deviation of 2, corresponding to an effective radius of 2 µm, and the spatially invariant and timeconstant refractive index of the GEISA-HITRAN dust-like data set, gathered by Massie (1994) and Massie and Goldman (2003) from measurements by Volz (1972Volz ( , 1973 and Shettle and Fenn (1979) on transported Saharan dust.…”
Section: The Forward Modelmentioning
confidence: 99%